Penggunaan Berbagai Dekomposer pada sampah Pasar untuk Tanaman Cabai (Capsicum annuum) - Syafrinal ' (Jurnal Sagu, 2007)
Utilization of organic waste for fertilizer can be enhanced by decomposer substances such as biotic or abiotic decomposers. A field experiment had been conducted to determine the impact of various kinds of decomposers applied to organic waste on chilli growth and production. The decomposer used including Trichoderma sp, stardec, EM-4 and M-Bio and assigned in the field by randomized block design. The result indicated that among decomposers used, EM-4 greatly enhanced decomposition as it promoted better plant growth and greater yield of the chilli. Key words: decomposer, organic waste, Capsicum annuum